ENTERPRISE ARCHITECTURE PLANNING (EAP) AS A STRATEGIC PLAN FOR INFORMATION SYSTEM MANAGEMENT TO IMPROVE THE SERVICE QUALITY FOR MULTAZAM VOCATIONAL SCHOOL IN GISTING - Fauzi Fauzi; Siti Mukodimah; Abdul Hamid (Jurnal TAM (Technology Acceptance Model), 2022)
Information technology is moving more and more forward and developing from time to time. One of the roles of information technology which is growing is the use of information technology to improve the governance of educational institutions from high schools to universities. Every educational institution is required to have models and standards which can be implemented as a basis for improving the alignment between business strategy and information technology. Enterprise Architecture Planning or commonly called (EAP) is one method which can be applied in making information architecture plans. The stages in EAP consist of data architecture, application architecture, technology architecture, and designs which have been made and can be implemented to support the achievement of the organization's mission. The system design uses flowchart design, use case diagrams, and class diagrams. Research conducted at Multazam Vocational School in Gisting resulted in a strategic design. The information system of Multazam Vocational School in Gisting is based on Android as an effort to improve service quality. With good management of information systems at Multazam Vocational School in Gisting, it will make easier for all parties to interact. The school can provide information to prospective students to access information easily. All the information needed by the community can be easily obtained without having to come directly, and enough with a smartphone and online.